2017
DOI: 10.4038/sljch.v46i4.8378
|View full text |Cite
|
Sign up to set email alerts
|

A study on incidence and associated factors of retinopathy of prematurity in a tertiary care setting in Sri Lanka

Abstract: Introduction: Retinopathy of prematurity (ROP) chiefly affects preterm infants. With the increased survival of extremely preterm infants, the number of infants with severe ROP has also increased.Objective: To assess the incidence, associated factors and outcome of ROP in neonates born at less than 34 weeks of gestation and/or less than 1.5 kg birth weight in Sri Jayawardenepura General Hospital Method: A prospective, descriptive, observational study was conducted in neonates born from 01/01/2014 to 31/12/2014,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…One study done in severely sight impaired children attending schools for the blind in Sri Lanka 9 revealed ROP accounts for major proportion of bilateral avoidable causes of blindness (34.9%) 9 . Another study done in neonatal intensive care unit of Sri Jayawardhanapura General Hospital Sri Lanka from 01.01.2014 to 31.12.2014 revealed institutional incidence of ROP 24.8% (28/113) in neonates screened 34 weeks or less period of gestation and/or 1.5 kg of birth weight while 42.9% of diagnosed ROP (12/28) or 10.7% of total screened (12/113) required ROP treatment 2 . Whereas Abeysekara et al, 2014 reported a higher rate of ROP incidence 37.6% (214 out of all 568 screened neonates in Lady Ridgeway Hospital for Children Sri Lanka) in which 18.7% (106/568) needed ROP treatment 10 .…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…One study done in severely sight impaired children attending schools for the blind in Sri Lanka 9 revealed ROP accounts for major proportion of bilateral avoidable causes of blindness (34.9%) 9 . Another study done in neonatal intensive care unit of Sri Jayawardhanapura General Hospital Sri Lanka from 01.01.2014 to 31.12.2014 revealed institutional incidence of ROP 24.8% (28/113) in neonates screened 34 weeks or less period of gestation and/or 1.5 kg of birth weight while 42.9% of diagnosed ROP (12/28) or 10.7% of total screened (12/113) required ROP treatment 2 . Whereas Abeysekara et al, 2014 reported a higher rate of ROP incidence 37.6% (214 out of all 568 screened neonates in Lady Ridgeway Hospital for Children Sri Lanka) in which 18.7% (106/568) needed ROP treatment 10 .…”
Section: Research Articlementioning
confidence: 99%
“…Retinopathy of prematurity (ROP) is a retinovascular disease of preterm, low birth weight neonates who were treated with oxygen and exposed to other risk factors as well 1,2 . Since the disease was first described by "Terry" in 1942 its management has greatly evolved to prevent childhood blindness 1,3,4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several risk factors are involved, including short gestation, low birth weight, phototherapy, blood transfusion, mechanical ventilation, surfactant therapy [5], oxygen therapy, its duration, low Apgar at 1 and 5 minutes, poor postnatal weight gain, intraventricular haemorrhage, sepsis, multiple pregnancy and anaemia [5,6]. A study done at a tertiary referral centre in Sri Lanka showed that there was a significant association of patent ductus arteriosus, sepsis, prolonged invasive ventilation and oxygen therapy for more than seven days with the occurrence of ROP [7].…”
Section: Introductionmentioning
confidence: 99%